Indonesia’s School Reform in Dealing with Public Education of Infected Area - Budi Ilham Maliki; Dewi Surani; Malik Fatoni; Mohamad Bayi Tabrani; Jaka Wijaya Kusuma (Enrichment : Journal of Management, 2021)
The implementation of our education to date still faces a big challenge, especially in terms of access to education for all those who have not been fair, the uneven quality of education, the allocation of budgets and the seriousness of local government in improving the quality of education that is still frail. Therefore, it is significant to reform for providing qualified, accessible, and affordable schools for all including for communities in leading, outer and retarded areas.This research aims to find out how to reform Indonesia's schoolsin dealing with public education of the outer most regional communities? To achieve this goal, researcher uses study research method or library studies which contain theories relevant to research problems. By using this method, an assessment of concepts and theories is used based on the available literature.The results of the library studies state that Indonesia's schools reforms in dealing with public education of the outer most regional communities by expanding access and improving the quality of education through several ways. First, the increase in the capacity of educational institutions. Second, the improvement of education equality through increased effectiveness of affirmative policy, as well as the provision of special scholarships for the poor and the implementation of quality distance education. Third, the provision of operational costs to improve the effectiveness of education. The policy carried out by the Ministry of Education and Culture in order to accelerate development in the 3T areas (leading, outer and retarded areas) is an advanced program together to educate Indonesia. This program includes An Integrated Teacher Professional Education program with Additional Authority (PPGT or Integrated Teacher Education Program), Bachelor's Program of Educating in 3T areas (leading, outer and retarded areas) or people also call as SM3T (Bachelor's Degree in Leading, Outer, and Disadvantaged Areas), Frontline Teachers (GGD), Regional Development Program, and Collaborative Integrated Teacher Professional Education (Integrated Teacher Education Program Collaboration).In conclusion, Indonesia's education reforms in dealing with the education of the outer most local communities are to expand access and improve the quality of education with advanced program policies together to educate Indonesia which includes Integrated Teacher Professional Education program with Additional Authority (PPGT), Bachelor Program of Educating 3T areas (leading, outer and retarded areas)or (SM3T), Front Line Teacher (GGD), Regional Development Program, and Collaborative Integrated Teacher Professional Education (Integrated Teacher Education Program Collaboration).